A fine balance and a shared learning journey: Exploring healthcare engagement through the experiences of youth with Neuromuscular Disorders - Travlos, V.; Bulsara, C.; Patman, S.; Downs, Jennepher (IOS Press, 2016)
BACKGROUND: Youth with Neuromuscular Disorders (NMD) who are wheelchair users can now survive well into adulthood if their multisystem comorbidities are prudently managed. Uptake of health behaviors may optimize their health outcomes. OBJECTIVE: To explore youths' perceptions of health, health behaviors and healthcare engagement. METHODS: This qualitative study purposefully recruited 11 youth with NMD from a concurrent, population-based study for variability of age, gender, type of NMD and their ratings of motivation and engagement. Interview data were analyzed and synthesized by thematic content. RESULTS: Participants perceived healthcare engagement as being given tools (knowledge and responsibility) and using them to maintain their finely balanced health. Nested in adequate social, emotional and physical support, they took responsibility for creatively integrating health behaviors they felt were informed by credible knowledge, gained primarily through personal experience. CONCLUSION: Cognizant of their compromised health, youth with NMD in this study were motivated to maintain their physical health. Limited NMD condition specific knowledge challenged youths' uptake of health behaviors. They valued a learning partnership with their healthcare professionals. By embracing the youth's experience based knowledge and through facilitating supportive relationships, healthcare professionals co-construct youth's healthcare engagement that may optimize health behaviors and outcomes.